(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Thin-walled and sheet materials with regular through holes (perforation) have wide practical application in various fields, including in medicine for the manufacture of implants, trays for placing and storing cutting instruments, sterilization of consumables. Perforated metal materials (PMM), primarily made of titanium and stainless steel, are of the most attention to specialists in the field of medical engineering, since they are characterized by lower weight, high strength and biomechanical compatibility. The mechanical characteristics of PMM are determined by the initial properties of the material, the dimensions of the sheet or tape, the shape and total area of the perforation. If selected correctly, dimensions and area of the perforations can provide optimal flexibility and plasticity with a significant reduction in the weight of the implant. This paper presents properties of perforated plates made of stainless steel, obtained by non-destructive methods. In particular, the dependences of the Lamb wave velocities at different frequencies on the specific total area of the plate’s perforation are shown. The data of elastic properties dependences on the perforation area. The data of microscopic studies of changes in the quality of holes obtained by laser cutting are also presented.